Learning from your mistakes: The functional value of spontaneous error monitoring in aphasia - Erica L. Middleton; Nazbanou Nozari; Maureen Gagliardi; Kelly M. Garvey (Frontiers in Psychology, 2014)
Self-monitoring of errors in picture naming has been shown to correlate positively with aphasia treatment outcomes (Marshall et al., 1994). To explore potential explanations, we took advantage of aphasics’ item-level inconsistency in naming accuracy, e.g., in the baseline phase of treatment studies. We looked for a “monitoring benefit” such that items erroneously named on baseline 1 would be more likely to be named correctly on baseline 2 if accompanied by spontaneous monitoring, relative to unmonitored errors. Such a monitoring benefit might reflect learning (e.g., in response to the self-generated error signal) and/or the differential strength (e.g., proximity to threshold) of monitored items compared to those that are not monitored. To implicate learning requires evidence that the monitoring benefit is directionally asymmetric, i.e., the monitoring-related change in accuracy from baseline 1 to 2 (forward direction) is greater than the monitoring-related change from baseline 2 to trial 1 (backward).